DIVERSITY AND CORRELATION OF BODY LENGTH DIMENSIONS OF BALI CATTLE AT THE BALI CATTLE BREEDING CENTER, GEROKGAK, BULELENG, BALI - Sigiro, Meilendry Angelina; Sampurna, I Putu; Suatha, I Ketut (Buletin Veteriner Udayana; Vol. 15 No. 1 February 2023DO - 10.24843/bulvet.2023.v01.i01.p10, 2022)
Bali cattle are one of the original cattle breeds in Indonesia. Selecting to produce good offspring is an important factor in bali cattle management. In selecting bali cattle, the diversity and correlation between body length dimensions can be used as a benchmark. The potential of the bali cattle population in Gerokgak makes it possible to apply for certification as a source area for bali cattle so that it can become a certified superior bali cattle model. This research was conducted by measuring the length of the head, neck, body, ears, tail, and horn on 25 cattles at Pusat Pembibitan Sapi Bali Unggul Gerokgak by purposive sampling method. The data obtained were analyzed by descriptive analysis and biplot analysis, presented in the form of tables and graphs. The results of the most diverse diversity of length dimensions are horn length, which is 18.2082% and the most similar is the head length of 4.9797%. Body length is positively correlated with head length, therefore in selecting bali cattle, head length can be used as an alternative to determine the classification of superior breeds of cattle and breeders are advised to pay attention to internal and external factors in the maintenance of bali cattle.